Heart rate and heart rate variability of Yo-Yo IR1 and simulated match in young female basketball athletes: A comparative study - Abad, C. C. C.; Pereira, L. A.; Kobal, R.; Kitamura, K.; Cruz, I. F.; Loturco, I.; Nakamura, F. Y. (International Journal of Performance Analysis in Sport, 2016)
To verify the cardiac autonomic response following the Yo-Yo IR1 and simulated basketball matches (SM) 20 young female Brazilian basketball players (16.92±1.07 years; 179.60±9.27 m; 73.33±15.71 kg; BMI = 22.59±3.56) performed the Yo-Yo intermittent recovery test (Yo-Yo) and the SM. Heart rate (HR) and heart rate variability (HRV) were monitored continually 10-min before, during, and 10-min after both experimental sessions. Global HRV indexes, measured maximal heart rate (HRmax), and several estimated HRmax were assessed. The time duration of Yo-Yo IR1 was lower than SB (6.12 ± 1.81 and 24.21 ± 4.04 min, respectively; ES=5.78). Higher values of measured-HRmax were registered in SM (195.27±8.40 beats.min-1) than during Yo-Yo IR1 (187.47±9.54 beats.min-1; ES=-0.93). No differences were found between the mean HR of the efforts (177±9 and 173±10 beats.min-1 for Yo-Yo and SM, respectively; ES =0.20). The six estimated HRmax ranged from 92.31±4.59 to 102.59±4.41% of the measured HRmax. Higher cardiac autonomic depression was found after SM. The technical-tactical requirement during the SM seemed to be able to reach HRmax but with lower cardiac autonomic response than Yo-Yo. This information may help coaches and physical conditioners to evaluate, prescribe and monitor training sessions regarding HR and HRV responses during common team sports practices.